Investigation of Marketing Strategies of Small and Medium Scale Enterprises (SMEs) in India: Case of Auto Part Firms in Punjab (India). - Bansal, Bharat (2010)
Marketing is a very important function in business management and plays a vital role in the success of any organisation. But most of the research into marketing has focussed on large scale organisations which have the scale and motive to manage marketing activities. SMEs play a vital role in the almost all regional economies and also in the global economy. They are the backbone of a society and account for most of the employment and productivity in any country. Yet, research into management of SMEs is quite limited. It is widely believed that business management approaches of SMEs and large scale organisations vary a lot and marketing function is one of these aspects which is different between SMEs and large scale organisation. Nevertheless, the significance of marketing cannot be ignored. This research investigates the marketing strategies of SMEs in developing nations using auto part manufacturers in the Indian State of Punjab as case study. This research uses a mixed research strategy and data was collected using structured questionnaires and semi structured interviews. This research finds that the SMEs mainly rely on word of mouth marketing and relationship marketing. SMEs tend not to use mass media for advertising and SMEs in developing countries also lack the usage of electronic media for marketing purposes. This research also finds that the main focus of SME’s marketing strategy in developing nations are the intermediaries and not the end consumers because intermediaries play a vital role in the purchase decision of the consumer as the end consumers are information poor.